Analisis Tingkat Penyerapan Tenaga Kerja di Karesidenan Surakarta - Siti Aisyah; Indan Nur Pratiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
This study aims to analyze the effect of government spending, GDRP, minimum wage, inflation and human development index on employment in Surakarta Residency. The analytical method used in this study is panel data regression, which is a combination of cross section data (seven regencies / cities in Surakarta Residency) and time series data for 10 years (2008-2017). The data used was obtained from the official website of the Central Statistics Agency (BPS). Based on the analysis of the Chow Test and the Hausman Test the best model chosen was the Fixed Effect Model (FEM). Using the significance level of 0.10 the result showed that the variable of government expenditure and HDI have a positive and significant effect on employment in Surakarta Residency, while the GDRP, minimum wage, and inflation have no effect on labor absorption in Surakarta in 2008-2017